(untitled) (Research, Society and Development, 2022)
According to current evidence, anxiety is perceived in individuals, increasingly, leaving the parameter of normality and becoming pathological. Meditation, an ancient practice, in turn, has been more used in contemporary times. Thus, this study was carried out with the aim of investigating the relationship between anxiety and meditation and its use to reduce anxiety and all its effects and consequences. The methodology consisted of an integrative exploratory literature review, carried out through steps that identified the theme; defined inclusion and exclusion criteria for the research; defined the information extracted from the articles; they categorized the studies; evaluated; and presented the result of the review. It was observed that meditation has been used in addition to just reducing anxiety, but also for treatment or intervention in other health complications, such as fibromyalgia, depression and cardiovascular diseases, for example, in addition to being used in different populations, as university students, adults and seniors. Finally, it was concluded that meditation is an alternative, integrative and complementary tool that encompasses body and mind, assists in mindfulness in the now, avoiding apprehension for fear of what is to come, consolidating itself as an instrument that can help with anxiety.